(3GdbSWGS aj GdefWbs - (3GdSeQbfOj , TeS GdOjf eMeO Hf GTQa GdMSjfj GdSeQbfOj,J (B690 (3g` s ((3eMeO GdShc s)
(3ChdgG (B:s
(3jHJOF HJQJjH GdHMK hJhLjg GdCSFdI hGdCLhHI Cbhd dENaGA ai GdHMK EfeG jbY ajeG ajg Mce eG s
(3BNQgG (B:s
(3Mdg deKd eG eQ EP dGjdRe ef YOe EfJbGA LejY GdCTjGA Ydi gPG GdJbOjQ dRhe HYV EfJbGA GdCTjGA dgPG GdJbOjQ GfJgi cJGH bSWGS GdCacGQ s
(3Ydjg bQGAg GHf fgjO Ydj eMeO Hf eMeO Hf Rfcj GdCQZjGfj GdCSaQGjjfj SfI (B717 (3g` hNW GHf Rfcjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B39 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B63s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1326s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdadSaI hGdefWbs